Case report of three cases and literature review: is follicular occlusion triad with peripheral/axial spondyloarthritis involvement an analog of SAPHO syndrome? - Dongdong Zhao; Jinwan Du; Ran Man; Shaohui Geng; Shike Shang; Chen Li (Frontiers in Medicine, 2026)
Background SAPHO syndrome is a rare chronic rheumatic disease characterized by five typical manifestations: synovitis, acne, pustulosis, hyperostosis, and osteitis. The follicular occlusion triad (FOT) comprises hidradenitis suppurativa (HS), acne conglobata (AC), and dissecting cellulitis of the scalp (DCS). The associations of FOT with peripheral/axial spondyloarthritis remain poorly understood. This study aimed to delineate the pattern of possible peripheral/axial spondyloarthritis involvement in patients with FOT. Methods All cases of FOT with peripheral/axial spondyloarthritis treated at our center were reported and compared with previously reported cases from the literature. Epidemiological and clinical data were collected from these cases. Results Three cases of FOT with peripheral/axial spondyloarthritis from our center and 10 cases from the literature review were included. We confirmed the FOT diagnosis in these patients and analyzed their associated spondyloarthritis involvement. The clinical features and treatments of these cases were also summarized. Most patients were male (92.31%, 12/13). In all patients, skin lesions preceded the onset of spinal arthritis, with intervals ranging from 0.6 to over 15 years. Symptoms related to axial arthritis typically presented as cervical and/or lumbar pain and stiffness (46.15%, 6/13). Only a few patients exhibited the typical sternoclavicular involvement seen in SAPHO syndrome (15.38%, 2/13). Laboratory examinations revealed elevated inflammatory markers and negative rheumatoid factor/HLA-B27 in all patients. Prednisone and adalimumab were reported to provide prolonged remission, while one patient responded satisfactorily to isotretinoin treatment. Conclusion We provide an updated overview of the disease pattern of peripheral/axial spondyloarthritis involvement in patients with FOT.